The discursive (de)legitimisation of global governance: political contestation and the emergence of new actors in the WTO's Dispute Settlement Body. Issue 3 (2nd July 2016) - Strange, Michael
Abstract : The World Trade Organization's Dispute Settlement Body provides the teeth of the global trade regime – empowering it with substantial means to adjudicate in disagreements between Member-states over the implementation of WTO law. The WTO's teeth have, however, also helped make the organisation controversial. The Dispute Settlement Body has frequently found itself at the centre of a much wider societal critique of the broader WTO – as well as contemporary global trade governance – in which its legitimacy to operate has been fiercely questioned. The political sensitivity of its work has been made most apparent in those cases where the principles of WTO law appear to run counter to environmental or consumer safety concerns, taking the system into the mass media and making it the subject of street protests. Yet, where rulings have given new access to non-state actors campaigning for these concerns (e.g. amicus curiae provisions), there has been further controversy amongst Member-states over whether the Dispute Settlement Body has acted outside its delegated authority by effectively rewriting 'who' or 'what' is an actor in the system. The changing character of this specific institutional arrangement is approached in the article as part of a wider struggle over the terms of what is 'legitimate' in global governance. Where WTO Dispute Settlement has been re-politicised, both inside and outside the formal institution, a contradiction becomes visible – between its legal-technocratic identity and a world that is fundamentally political. The legal normalisation of new actor identities needs to be understood in this context, as an attempt to manage that tension and reinforce the claim that WTO Dispute Settlement is legitimate. How the institution has changed and new identities emerged since its birth in 1995 is enhanced if understood in the context of a struggle in which the terms of what is legitimate in global governance are ultimately unfixed.